Measuring resting cerebral haemodynamics using MRI arterial spin labelling and transcranial Doppler ultrasound: Comparison in younger and older adults. Issue 7 (25th May 2021) - Burley, Claire V.; Francis, Susan T.; Whittaker, Anna C.; Mullinger, Karen J.; Lucas, Samuel J.E.
Abstract: Introduction: Resting cerebral blood flow (CBF) and perfusion measures have been used to determine brain health. Studies showing variation in resting CBF with age and fitness level using different imaging approaches have produced mixed findings. We assess the degree to which resting CBF measures through transcranial Doppler (TCD) and arterial spin labeling (ASL) MRI provide complementary information in older and younger, fit and unfit cohorts. Methods: Thirty‐five healthy volunteers (20 younger: 24 ± 7y; 15 older: 66 ± 7y) completed two experimental sessions (TCD/MRI). Aging and fitness effects within and between imaging modalities were assessed. Results: Middle cerebral artery blood velocity (MCAv, TCD) was lower and transit time (MRI) slower in older compared with younger participants ( p  < .05). The younger group had higher gray matter cerebral perfusion (MRI) than the older group, albeit not significantly ( p  = .13). Surprisingly, fitness effects in the younger group (decrease/increase in MCAv/transit time with fitness, respectively) opposed the older group (increase/decrease in MCAv/transit time). Whole cohort transit times correlated with MCAv (r=−0.63; p  < .05), whereas tissue perfusion did not correlate with TCD measures. Conclusion: TCD and MRI modalities provide complementary resting CBF measures, with similar effects across the whole cohort and between subgroups (age/fitness) if metrics are comparable (e.g., velocity [TCD] versus transit time [MRI]). Abstract : We assess the degree to which resting CBF measures from transcranial Doppler (TCD) and arterial spin labeling (ASL) MRI provide complementary information in older and younger, fit and unfit cohorts. Middle cerebral artery blood velocity (MCAv, TCD) was lower and transit time (MRI) slower in older compared with younger participants, though fitness effects in the younger group opposed those in the older group. Whole cohort transit times correlated with MCAv, whereas tissue perfusion did not correlate with TCD measures.